Breast Cancer Treatment Relying on Herbal Bioactive Components - Keshamma E.; Kumar, Anil; Jha, Ritesh; Amle, Vandana Sonaji; Dudhate, Gitanjali Sambhajirao; Patel, Divyakant; Saha, Purabi; Kumar, Roshan (Journal for Research in Applied Sciences and Biotechnology, 2022)
Use of herbs and plants in cooking and medicinal dates back thousands of years. In this overview, we look at the many plant species that still have immune-boosting and cancer-fighting properties. Carotenoids, flavonoids, ligands, polyphenolics, terpenoids, sulphides, lignans, and plant sterols are only some of the many active phytochemicals found in different types of herbs. There are a number of mechanisms through which these phytochemicals exert their effects. They either prevent cell division or stimulate the synthesis of a protective enzyme such as glutathione transferase. The cancer-fighting and cholesterol-lowering effects of mevalonate are counteracted by the volatile oils and plant extracts from various herbs and plants.